2012
DOI: 10.1093/humrep/des375
|View full text |Cite
|
Sign up to set email alerts
|

Long-term reproductive outcomes in women whose first pregnancy is ectopic: a national controlled follow-up study

Abstract: All the expenses were covered by Gynaecological Clinic, Rigshospitalet. Ø.L. has within the last 3 years received honoraria for speeches in pharmacoepidemiological issues. L.L.K., P.E. and C.W.S. had no conflict of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
4
21
1
Order By: Relevance
“…A Danish study found that the probability of intrauterine pregnancy increased over time for women with an ectopic first pregnancy (5), a finding compatible with the trends in the last time period of our study. Advancements in both treatment of ectopic pregnancy and assisted reproductive technology have likely improved the ability of women to achieve an intrauterine pregnancy (1,2,4,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Danish study found that the probability of intrauterine pregnancy increased over time for women with an ectopic first pregnancy (5), a finding compatible with the trends in the last time period of our study. Advancements in both treatment of ectopic pregnancy and assisted reproductive technology have likely improved the ability of women to achieve an intrauterine pregnancy (1,2,4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Although women with a history of ectopic pregnancy are at risk for repeated ectopic pregnancies (1)(2)(3), little is known on the outcomes of future intrauterine pregnancies. Most research has focused on the ability of women with a previous ectopic pregnancy to achieve an intrauterine pregnancy (4,5) or on optimizing treatment methods to preserve fertility (3,6). Improvements in diagnosis and treatment and the increased availability of assisted reproductive technologies have increased the likelihood that women with a history of ectopic pregnancy will achieve a future intrauterine pregnancy (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have mainly analyzed short‐term fertility according to different treatment methods . We recently described a compromised long‐term fertility prognosis in women whose first pregnancy was ectopic , but we found no study assessing the development over time as regards the long‐term reproductive prognosis in women after an ectopic pregnancy. Reproduction is influenced by women's intention to become pregnant, and by the availability of effective fertility treatment.…”
Section: Introductionmentioning
confidence: 92%
“…We recently described a compromised long-term fertility prognosis in women whose first pregnancy was ectopic (9), but we found no study assessing the development over time…”
Section: Introductionmentioning
confidence: 96%